INFLUENCE OF PARENTAL ATTITUDE ON THE MENTAL DEVELOPMENT OF PRIMARY SCHOOL STUDENTS: parental attitude; children; junior schoolchildren; mental development; junior students - Polukhina, Maryna; Anpilohova, Tetiana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article presents the results of theoretical and empirical research of the influence of parental attitude on the mental development of primary school children. The aim of the article is to study the features of parent-child relationships as a prerequisite for the formation of the child’s personality and mental development. Theoretical analysis of the problem showed that the attitude of parents to the child is especially important during all childhood years, especially during age crises, in particular, during primary school age and is realized in maintaining emotional contact with the child, a form of control over his/her behavior, effective-evaluative, consciously-selective idea of ​​the child, which determines the peculiarities of parental perception, the nature and manner of communication with the child, methods of influencing the kid. An empirical study of the influence of parental attitudes on the mental development of junior students was conducted among students in grades 2-4 aged 8-10 years using psychological techniques: the method of "Test-questionnaire of parental attitudes (ORO)" (A. Varga, V. Stolin), which explores the emotional attitude to the child (acceptance-rejection), socially desirable image of parental attitude (cooperation), interpersonal distance in communication with the child (symbiosis), the form and direction of control over its behavior, the attitude of parents to the failures of the child; the projective method "Picture of the family" reflects the child’s attitude to the family as a whole and to its individual members and his/her perception of own place in the family; "PARI" method (E. Schaefer, R. Bell) is designed to study the attitude of parents to various aspects of family life (family role). Empirical research results have shown that a favorable family environment, harmonious relations between spouses, a constructive type of parental attitude in which the child is free from excessive custody or control, and parents accept and understand the child, seek to be friends and advisers, flexibility in communication and means influence on the child in view of the age, positively affect the emotional state and the formation of individual and personal qualities of the child, the relationship with parents. Children with adequate parental practice are characterized by good adaptation to the school environment and communication with peers, they are active, independent, proactive, friendly, empathetic. The destructive influence of parental attitudes on children increases in those families where at least one of the adults is experiencing emotional distress